2020
DOI: 10.3390/ijms21238898
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling in Oesophageal Adenocarcinoma Cell Lines and Patient Serum Samples Reveals a Role for miR-451a in Radiation Resistance

Abstract: Many patients with Oesophageal Adenocarcinoma (OAC) do not benefit from chemoradiotherapy treatment due to therapy resistance. To better understand the mechanisms involved in resistance and to find potential biomarkers, we investigated the association of microRNAs, which regulate gene expression, with the response to individual treatments, focusing on radiation. Intrinsic radiation resistance and chemotherapy drug resistance were assessed in eight OAC cell lines, and miRNA expression profiling was performed vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…Numerous TP53 mutations are described for OAC cell lines (summarized in supplementary data of [ 50 ]). In our JH-EsoAd1 cell line model, the missense c797G>A mutation in TP53 resulting in an amino acid change of G266E is classified as “non-functional” [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous TP53 mutations are described for OAC cell lines (summarized in supplementary data of [ 50 ]). In our JH-EsoAd1 cell line model, the missense c797G>A mutation in TP53 resulting in an amino acid change of G266E is classified as “non-functional” [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several of the pathways that we identified as enriched in validated targets of miR-27a-3p are known to play an important role in mediating responses to treatment. For example, we identified a variety of different pathways all associated with lipid metabolism, which were also identified in our previous study of intrinsic radiation and drug resistance in a panel of eight OAC cell lines [ 50 ]. Other authors have associated lipid metabolic pathways with cancer cell survival and radiotherapy response, and suggested that these pathways are potentially promising targets for anti-cancer strategies [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations